Vertical Well Assisted Hydraulic Fracturing in Mudstone Interlayer of Terrestrial Ultra-heavy Oil Reservoir. Issue 1 (1st January 2023) - Wang, Qiqi; Chen, Mian; Lin, Botao; Huang, Yong; Chen, Sen
Abstract: The widely developed impermeable interlayers hinder the migration of steam and condensate in a steam stimulation project, bringing the difficulty of developing the formation part overlying the interlayer. Hydraulic fracturing the interlayer through an existing neighboring observation (vertical) well can break through the interlayer without significantly increasing the budget. In this study, the laboratory test results of true triaxial hydraulic fracturing experiments and CT tests were analyzed to investigate the fracture propagation in the oil sand-mudstone multi-layer samples. A geological model was established to simulate the crack expansion using the finite element (FE) method by employing the cohesive element to represent fracture apertures. Furthermore, the geological model after the fracturing treatment was imported to a thermo-hydro-mechanical simulator to predict its mechanical and production behavior under steam circulation. It was found from laboratory experiments that the hydraulic fractures that initiated in the mudstone layer effectively propagated into the oil sand layer. The FE simulation shows that vertical fractures can be formed under field stress conditions. The fracture would extend into the overlying and underlying oil sand layers passing through the lithological interface. Accordingly, the fractures caused by hydraulic fracturing treatment can accelerate the diffusion of injected steam and the flow of crude oil after substantial viscosity reduction by steam heating. Future research is dedicated to generating a more complex fracture network in the mudstone interlayer so that the oil and steam flow paths can be strengthened considerably.